THE ROLE OF SUSTAINABLE BUSINESS PRACTICES IN DRIVING LONG-TERM PROFITABILITY: A COMPARATIVE ANALYSIS OF GREEN INNOVATION - Sofiane Boudjema (Modern American Journals, 2025)
In recent years, sustainability has become a central focus in the business world, with increasing attention on how companies can achieve long-term profitability while adhering to environmentally responsible practices. Green innovation, a key component of sustainable business practices, plays a critical role in driving profitability by enhancing operational efficiency, reducing costs, and appealing to environmentally conscious consumers. This paper examines the role of sustainable business practices, specifically green innovation, in fostering long-term profitability. Through a comparative analysis of case studies from leading organizations that have implemented green innovations—such as renewable energy adoption, eco-friendly product development, and sustainable supply chains—the paper explores how these practices contribute to both financial performance and corporate reputation. The research also identifies key challenges in integrating sustainability into business strategies and offers insights into how companies can overcome these barriers to achieve sustained growth.
Keywords: Sustainable Business Practices, Green Innovation, Long-Term Profitability, Corporate Sustainability, Renewable Energy, Eco-friendly Products, Supply Chain Sustainability, Business Strategy, Environmental Responsibility, Competitive Advantage